Does Integrated Fixation Provide Benefit in the Reconstruction of Posttraumatic Tibial Bone Defects?. Issue 10 (October 2015) - Bernstein, Mitchell; Fragomen, Austin T.; Sabharwal, Samir; Barclay, Jonathan; Rozbruch, Robert S.
Abstract: Background: Limb salvage in the presence of posttraumatic tibial bone loss can be accomplished using the traditional Ilizarov method of distraction osteogenesis with circular external fixation. Internal fixation placed at the beginning of the consolidation phase, so‐called integrated fixation, may allow for earlier removal of the external fixator but introduces concerns about cross‐contamination from the additional open procedure and maintenance of bone regenerate stability. Questions/purposes: Among patients deemed eligible for integrated fixation, we sought to determine: (1) Does integrated fixation decrease the time in the external fixator? (2) Is there a difference in the rate of complications between the two groups? (3) Are there differences in functional and radiographic results between integrated fixation and the traditional Ilizarov approach of external fixation alone? Methods: Between January 2006 and December 2012, we treated 58 patients (58 tibiae) with posttraumatic tibial bone loss using the Ilizarov method. Of those, 30 patients (52%) were treated with the "classic technique" (external fixator alone) and 28 (48%) were treated with the "integrated technique" (a combination of an external fixator and plating or insertion of an intramedullary nail). During that period, the general indications for use of the integrated technique were closed physes, no active infection, and a healed soft tissue envelope located at the intended internal fixation site; the remainder of the patients were treated with the classic technique. Followup on 30 (100%) and 28 (100%) patients in the classic and integrated techniques, respectively, was achieved at a minimum of 1 year (mean, 3 years; range, 1‐8 years). Adverse events were reported as problems, obstacles, and complications according to the publication by Paley. Problems and obstacles are managed by nonoperative and operative means, respectively; in addition, they resolve completely with treatment. Complications, according to the Paley classification, result in permanent sequelae. Functional and radiographic results were reported using the Association for the Study and Application of Methods of Ilizarov scoring system. Results: Overall, there was a mean of four (range, 2‐5) surgical procedures to complete the tibial reconstruction with a similar incidence of unplanned surgical procedures (obstacles) between the two groups (p = 0.87). Patients treated with integrated fixation spent less time in the external fixator, 7 months (range, 5‐20 months) versus 11 months (range, 1‐15 months; p < 0.001). There were seven problems, 15 obstacles, and zero complications in the classic group. Ten problems, 15 obstacles, and one complication occurred in the integrated fixation group. There was no difference in the severity (p = 0.87) or number (p = 0.40) of complications between both groups. Good to excellent Association for the Study and Application of Methods of Ilizarov function and bone scores were obtained in 100% and 98% of patients, respectively. Conclusions: The integrated fixation method allows for a more efficient limb salvage surgical reconstruction in patients carefully selected for that approach, whereas the frequency of adverse events and ability to restore limb lengths was not different between the groups with the numbers available. Careful placement of external fixation pins is critical to decrease cross‐contamination with planned internal fixation constructs. In this study of posttraumatic tibial bone defect reconstruction, good/excellent results were found in all patients after a mean of four surgical procedures; however, a larger multicenter prospective study would allow for more robust and generalizable conclusions. Level of Evidence: Level III, therapeutic study.